Comparison of Performance, Egg Quality, and Egg Cost of Different Laying Genotypes in Free-Range System from 21 to 44 Weeks of Age - Ali Aygun; Doğan Narinç; Hasan Arısoy (Animals)
The aim of this study was to compare the performance, egg quality and economic aspects of laying hybrids of different genotypes in free-range system. In the study, three different laying genotypes (Lohmann Brown, Lohmann Sandy and ATAK-S genotype) were used. Each group consisted of four replicates and each replicate contained 20 hens. Egg production, broken–cracked egg ratio, egg weight, feed consumption, feed efficiency, and viability were determined as performance traits. Eggshell strength, Haugh unit, yolk color, and shell color were determined as egg quality traits. The costs of eggs were assessed for economic analysis. The Lohmann Sandy genotype produced more eggs than the Lohmann Brown genotype (p < 0.05). The ATAK-S genotype reached 50% egg production age sooner than other genotypes (p < 0.05). The Lohmann Sandy and Lohmann Brown genotypes produced fewer broken eggs and heavier eggs compared to the ATAK-S genotype (p < 0.05). The ATAK-S genotype consumed more feed than the Lohmann Sandy and Lohmann Brown genotypes (p < 0.05). The Lohmann Sandy and Lohmann Brown genotypes have better feed efficiency compared to the ATAK-S genotype (p < 0.05). Eggs from the Lohmann Sandy genotype exhibit greater resistance to breakage compared to those from other genotypes (p < 0.05). The highest quality of albumen was identified in the eggs of the Lohmann Brown genotype (p < 0.05). The yolk color of Lohmann Brown genotype eggs is darker than those of other genotypes (p < 0.05). The shell color of Lohmann genotype eggs is a darker brown compared to eggs of other genotypes (p < 0.05). The cheapest egg cost was determined from eggs produced from the Lohmann Sandy genotype (p < 0.05). According to the results obtained from our study, it would be more appropriate to prefer the Lohmann Sandy genotype in the free-range system.